2013
DOI: 10.3139/217.2714
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Taguchi Method for Optimization of Poly (Butylene Terephthalate) and Poly (Trimethylene Terephthalate) Blends through Injection Molding

Abstract: As tatistical experimental design method known as the Taguchi method was utilized to optimize the injection molding processes of poly(butylene terephthalate) (PBT) and poly(trimethylene terephthalate) (PTT) blends. Impact strength was taken as the optimized property. The significant parameters included mold temperature, injection pressure, holding pressure, injection time and holding temperature. Results of the Taguchi analysis gave mold temperatures as major influencing factor on the impact strength. The opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…[7][8][9][10][11] As a s e m i -c r y s t a l l i n e p o l y m e r , p o l y ( b u t y l e n e terephthalate) (PBT) has been widely used due to its advantages of certain rigidity, high crystallization rate, fatigue resistance, heat resistance and solvent resistance. [12][13][14] However, PBT has the disadvantage of insufficient toughness, especially the notched impact strength is not enough, and is limited in some applications. In order to improve its toughness, more attention has been paid in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] As a s e m i -c r y s t a l l i n e p o l y m e r , p o l y ( b u t y l e n e terephthalate) (PBT) has been widely used due to its advantages of certain rigidity, high crystallization rate, fatigue resistance, heat resistance and solvent resistance. [12][13][14] However, PBT has the disadvantage of insufficient toughness, especially the notched impact strength is not enough, and is limited in some applications. In order to improve its toughness, more attention has been paid in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer blending is one of the major techniques which can overcome these limitations. Through polymer blending it is possible to develop new and novel materials with attractive properties . There are several studies which have reported substantial improvement in mechanical, thermal, and barrier properties in blends compared to their individual polymers.…”
Section: Introductionmentioning
confidence: 99%
“…where y i is the OPD, LCD, or gray relational grade (see Section 3.3); y is the mean of y i , and n is the number of measured points in each trial. [29][30][31]…”
Section: Taguchi Optimization Analysismentioning
confidence: 99%
“…The aim of the Taguchi analyses was to minimize the OPD and LCD properties of the de‐molded PLA. Thus, for each optimization objective (i.e., OPD or LCD), the quality of the experimental outcome for each run in the Taguchi OA was evaluated using the following larger‐the‐better signal‐to‐noise ratio (S/N) characteristic: S/N=10logtruey¯2+Sn2, Sn=i=1nyiytrue¯2n, where yi is the OPD, LCD, or gray relational grade (see Section 3.3); normalytrue¯ is the mean of yi, and n is the number of measured points in each trial 29–31 …”
Section: Simulation Analysis Optimization Framework and Verification ...mentioning
confidence: 99%